Detection of organic pollutants, food additives and antibiotics using sustainable carbon dots. (16th April 2023) - Kaur, Inderbir; Batra, Vandana; Kumar Reddy Bogireddy, Naveen; Torres Landa, Simei Darinel; Agarwal, Vivechana
Graphical abstract: Highlights: Overview of green carbon dots (CDs) based optical sensing for the detection of organic contaminants. Green precursor derived CDs for the detection of organic pollutants, pesticides, food additives and antibiotics. Evaluation based on sensitivity and selectivity. Comparison of quantum yield, limit of detection, and linear concentration of range. Challenges and future perspectives discussed. Abstract: The ecosystem across the globe has been adversely affected due to the adoption of unsustainable growth strategies. Overuse of organic pollutants such as dyes, pesticides, disinfectants, food additives and antibiotics, along with their release into the environment without proper treatment has severely affected the food chain and water bodies, hence ultimately the human race. As the organic contaminants, being non-biodegradable, persist in the environment for a long duration, a sustainable method for the detection of these harmful organic pollutants is essential. For food safety and restoration of ecological balance, simple, non-toxic, cost-effective and environmentally friendly green precursor derived carbon dots (CDs) are favorable as compared to inorganic nanoparticles (CdTe, CdS etc.) and chemically derived CDs. This review covers the summary of the studies devoted to the optical detection of organic pollutants, food additives and antibiotics through green precursor derived CDs, reported during the last few years. The upcoming studies of optical sensing systems with sustainable CDs provide powerful insight towards pollutant detection, as well as act as a future monitoring tool.